Organizational Change Management and Its Influence on Employee Engagement in Regional Banks in Central Java - Zulkifli; Husnul, Andi (Maroon Journal De Management, 2025)
Organizational change management (OCM) is increasingly vital for regional banks in Central Java that face competition, regulatory adjustments, and rapid technological transformation. This study examines how OCM practices influence employee engagement, focusing on leadership, communication, training, and participation during change processes. A quantitative correlational design was applied with 220 respondents selected through proportional stratified random sampling from managerial and non-managerial staff. Data were gathered using structured questionnaires measuring OCM dimensions leadership support, communication transparency, employee participation, training, and readiness for change alongside employee engagement assessed by the Utrecht Work Engagement Scale. The analysis, conducted using descriptive statistics, Pearson correlation, and multiple regression in SPSS 25, revealed a significant positive relationship between OCM and employee engagement (r = 0.671, p < 0.01). Leadership and communication emerged as the strongest predictors, accounting for 45.6% of the variance in engagement. Employees demonstrated higher vigor and dedication when they experienced open communication and involvement in change initiatives. The findings highlight that effective OCM strengthens employee engagement, emphasizing the need for strong leadership, transparent communication, and participatory strategies to ensure successful change and sustained organizational performance.